Development of a fermented product with higher phenolic compounds and lower anti-nutritional factors from germinated lupin (Lupinus angustifolius L.) - Khan, M.; Karnpanit, W.; Nasar-Abbas, S.; Huma, Z.; Jayasena, Vijay (Wiley Online Library, 2018)
© 2018 Wiley Periodicals, Inc. The nutritional profile of lupin (Lupinus angustifolius L.) seeds has recently increased the scientific importance to develop variety of lupin-enriched food products. In this study, a fermented food product from lupin was developed as another product to Tempe (a fermented food product made from cereals) family for its improved nutrient profile. For this purpose, whole lupin seeds were subjected to germination at 25°C for 0, 3, 6, 9, and 12 hr. After dehulling and cooking, lupin seeds from each germination period were fermented using Rhizopus oligosporus. Fermentation significantly increased the phenolic contents and antioxidant potential by 300%–450% and 100%–300%, respectively. Decrease in phytate content from 14.2 to 4.7 mg/g DM and tannins from 0.88 to 0.07 mg CE/g DM were also noted. In conclusion, germination of seeds can be used as a pretreatment to obtain higher quantities of bioavailable phytochemical components in fermented lupin. Practical applications: The presence of different innovative food products in the market shows the commitment of food scientists to fulfill the consumer demand for food with high nutritive value. The process of fermentation is known to improve the nutrients’ profile, thus helps to meet the consumer demands. The nutritive importance of Australian sweet lupin is known well-demonstrated for its application in various food products. The outcome of this study could be of great importance to food industry for production of a novel-fermented food product with improved nutritional value from germinated lupin. The proposed product is relatively cheap compared with traditional Tempe made from soybean due to its lower agronomical production cost. The study could be extended to analyze protein digestibility and to improve the sensory acteristics of product for higher consumer acceptability.